Conditional indirect relations between executive functions, emotion regulation, and Machiavellianism in young men and women. (15th October 2020) - Fatima, Shameem; Shahid, Zoha
Abstract: The main focus of the current study was to assess direct and indirect associations between specific executive functions, emotion regulation strategies, and Machiavellianism. A secondary objective was to test whether gender moderates these indirect associations. The study used a correlational research design to achieve these objectives. There were 195 young adults (51% men) in age range between 19 and 25 years (M = 21.28, SD = 1.40), who were selected as the test sample. The participants were assessed on performance tests taken from Delis-Kaplan Executive Functions System for three executive function components namely inhibition, visuo-spatial construction ability, and cognitive flexibility, and on self-report measures of emotion regulation questionnaire and Mach IV for emotion regulation strategies and Machiavellian techniques. Results indicated that two of the three executive function components including inhibition and cognitive flexibility were associated with Machiavellianism. Moreover, only cognitive reappraisal but not expressive suppression strategy mediated these associations. Finally, conditional indirect associations between cognitive flexibility, cognitive reappraisal, and Machiavellianism were significant only for women but not for men.